Cognitive Analysis of Decision Support for Antibiotic Ordering in a Neonatal Intensive Care Unit - Sheehan, B.; Kaufman, D.; Bakken, S.; Currie, L. M. (Applied Clinical Informatics, 2012)
Background: Clinical decision support systems (CDSS) are a method used to support prescribing accuracy when deployed within a computerized provider order entry system (CPOE). Divergence from using CDSS is exemplified by high alert override rates. Excessive cognitive load imposed by the CDSS may help to explain such high rates. Objectives: The aim of this study was to describe the cognitive impact of a CPOE-integrated CDSS by categorizing system use problems according to the type of mental processing required to resolve them.Methods: A qualitative, descriptive design was used employing two methods; a cognitive walk-through and a think-aloud protocol. Data analysis was guided by Norman’s Theory of Action and a theory of cognitive distances which is an extension to Norman’s theory.Results: The most frequently occurring source of excess cognitive effort was poor information timing. Information presented by the CDSS was often presented after clinicians required the information for decision making. Additional sources of effort included use of language that was not clear to the user, vague icons, and lack of cues to guide users through tasks.Conclusions: Lack of coordination between clinician’s task-related thought processes and those presented by a CDSS results in excessive cognitive work required to use the system. This can lead to alert overrides and user errors. Close attention to user’s cognitive processes as they carry out clinical tasks prior to CDSS development may provide key information for system design that supports clinical tasks and reduces cognitive effort.
Keywords: NICU; clinical decision support; alerts; cognitive impact; antibiotics